Utilização de isótopos estáveis em ruminantes - Ducatti, Carlos [UNESP]; Martins, Cyntia Ludovico [UNESP]; Arrigoni, Mário de Beni [UNESP]; Martins, Marcela Buosi [UNESP]; Vieira Júnior, Luis Carlos [UNESP]; Denadai, Juliana Célia [UNESP] (My University, 2011)
The technique of stable isotopes has been used as a tool for the detection of adulteration in food. There are important advantages for the use of stable isotopes over conventional techniques. Naturally occurring as dietary indicators, besides the fact of their estimates are based on the isotopic dietary food assimilated and not just in food intake. Still, by this technique, information can be obtained from diets consumed the short and long periods, depending on the tissue evaluated. This review provides an overview of key elements isotopic used in studies in ruminants.

A técnica de isótopos estáveis tem sido utilizada como ferramenta para a detecção de adulteração em alimentos. Existem vantagens importantes para o uso de isótopos estáveis sobre as técnicas convencionais, pois naturalmente ocorrem como indicadores dietéticos, além do fato de suas estimativas dietéticas isotópicas basearem-se nos alimentos assimilados, e não apenas nos alimentos ingeridos. Com esta técnica também é possível obter informações de dietas consumidas a curto e longo períodos, dependendo do tecido avaliado. Esta revisão fornece uma visão geral dos principais isótopos estáveis utilizados em estudos com ruminantes.
Use of stable isotopes in ruminants
Keywords: Authenticity; Carbon; Hydrogen; Nitrogen; Oxygen; Traceability; Autenticidade; Carbono; Hidrogênio; Nitrogênio; Oxigênio; Rastreabilidade